Examining translation behaviour of Turkish student translators in scientific text translation with think-aloud protocols - Başer, Zeynep; Çetİner, Caner (Meta, 2022)
The process of translation has been dramatically influenced by the latest developments in technology. Students’ behaviours during the translation process have also changed as they try to seek information and use different resources. This study aims to investigate the translation behaviour of students in an English translation department. For this purpose, 11 students were recruited. The students were asked to translate a scientific text from English into Turkish. For the analysis of their translation behaviour, Think-Aloud Protocols (TAPs) and their translated texts were used. Monologue Protocol was used to see what goes on in a prospective translator’s mind. The students were audio-recorded while translating. Then, the translations were scored and the transcriptions of the recordings were coded. The results were presented under three main themes: (i) Recruiting translation tools: when and how, (ii) Following a pattern of translation process, and (iii) Challenges: language(s), context and more. All in all, the present study highlights the importance of guiding students in the use of the appropriate tools for the translation of specialised texts, and also suggests that student translators should be more critical of Machine Translation outputs and should practice post-editing procedures in their courses.